2018
DOI: 10.1186/s12864-018-5033-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of heat stress and lipopolysaccharide on the bursal transcriptome in two distinct chicken lines

Abstract: BackgroundExposure to heat stress suppresses poultry immune responses, which can increase susceptibility to infectious diseases and, thereby, intensify the negative effects of heat on poultry welfare and performance. Identifying genes and pathways that are affected by high temperatures, especially heat-induced changes in immune responses, could provide targets to improve disease resistance in chickens. This study utilized RNA-sequencing (RNA-seq) to investigate transcriptome responses in the bursa of Fabricius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 79 publications
0
45
0
Order By: Relevance
“…The Wnt/β-catenin pathway, or so-called canonical Wnt signaling, is well known for a signaling stream that is involved in chicken primordial germ cells development, specification, migration, and proliferation (Kimura et al 2006; Ohinata et al, 2009; Laird et al, 2011; Chawengsaksophak et al, 2012). Recent studies indicate that Wnt ligands and Wnt receptors are expressed in the bursa (Sun et al, 2015; Liu et al, 2016; Monson et al, 2018). In the current study, Frizzled ( FZD ) receptors FZD2, 7, 8, and 10 and Wnt co-receptors low-density lipoprotein-related proteins ( LRP ) LRP1, 2, and 4 were upregulated from ED16–ED19.…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt/β-catenin pathway, or so-called canonical Wnt signaling, is well known for a signaling stream that is involved in chicken primordial germ cells development, specification, migration, and proliferation (Kimura et al 2006; Ohinata et al, 2009; Laird et al, 2011; Chawengsaksophak et al, 2012). Recent studies indicate that Wnt ligands and Wnt receptors are expressed in the bursa (Sun et al, 2015; Liu et al, 2016; Monson et al, 2018). In the current study, Frizzled ( FZD ) receptors FZD2, 7, 8, and 10 and Wnt co-receptors low-density lipoprotein-related proteins ( LRP ) LRP1, 2, and 4 were upregulated from ED16–ED19.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, increased endotoxin concentration in the blood might lead to a vicious circle, impairing the gut barrier function, and finally, more endotoxin can translocate to the blood. Furthermore, one study describes the effect of heat stress combined with subcutaneous injection of 100 µg/kg LPS derived from Salmonella enterica typhimurium [ 62 ]. In accordance with our study, the combined treatment had the most pronounced impact on gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The inbred Fayoumi line included in this study has been shown to be relatively more resistant against various pathogens and environmental stresses than the inbred Leghorn line or a broiler line, including the Fayoumi line activating immune-related signaling pathways against viral infection and LPS treatment with/without heat stress [ 32 , 59 , 60 , 61 ]. In this study, we investigated the expression of 20 chicken HDPs before and after induction by LPS and poly(I:C) in embryonic fibroblasts and bone marrow-derived cells from the inbred Fayoumi M15.2 and Leghorn Ghs6 chicken lines.…”
Section: Discussionmentioning
confidence: 99%